(Invited) Nanoengineered Thermoelectric Energy Devices for IoT Sensing Applications. (3rd July 2019) - Ono, Takahito; Nguyen, Trung Huu; Samat, Khairul Fadzli; Li, Jinhua; Toan, Nguyen Van
Abstract : This paper reviews the work done by authors regarding thermoelectric power generators developed for energy-harvesting internet of thing (IoT) sensor applications. Materials and mass-producible process developments based on electrochemical process are conducted for thermoelectric power devices. In order to store the thermoelectric energy from a low-quality heat source, micro supercapacitors composed of graphene nanowall electrodes are developed. The fabrication process of a flexible thermoelectric power generators based on the electrochemical process has been developed.